Strategi Guru Taman Pendidikan Al-Qur’an Al-Falah untuk Meningkatkan Ahklak Anak Jorong Silaping Kecamatan Ranah Batahan Kabupaten Pasaman Barat - Zulya, Reska; Juliardi, Budi; Azwar, Azwar (Lembaga Yasin AlSys, 2023)
This research is motivated by a problem, namely: how to apply the strategies used by teachers of the Al-Qur'an education garden to improve children's morals. The purpose of this study was to describe the strategies used by teachers of the Al-Qur'an education garden to improve children's morals and what obstacles were found by the Al-Qur'an education garden teachers in improving children's morals. The type of research used was qualitative research using descriptive methods. There were 8 informants in this study including: TPA Al-Falah administrators, Head of TPA Al-Falah, third grade teachers, parents of children and children of TPA Al-Falah. Data collection techniques used are observation, interviews and documentation. Data processing with analysis of data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the strategy used by the Al-Qur'an education garden teacher to improve children's morals is by using methods as moral enhancement. Exemplary method, habituation method, practice method, story method, singing method, and punishment method. The obstacles found by Al-Falah TPA teachers to improve children's morals, namely the use of increasingly sophisticated technology, limited time for parents to develop children's morals, some teachers at TPA are sometimes absent from learning due to demands from their work or others, lack of religious teaching strong influence while at school, peer influence, and lack of parental supervision of their child's social interactions in the community. The results of the research above can be concluded that the application of exemplary methods, habituation methods, practical methods, story methods, singing methods, and punishment methods can improve the morals of children at TPA Al-Falah Jorong Silaping. This is done so that children have good morals towards peers, the surrounding environment, especially parents. By holding a TPA in the surrounding environment, it is hoped that it can help improve the morals of the children to become better individuals in the future.